Sistem Pendukung Keputusan Pemilihan Kamar Kost Mulyadi Dengan Metode Simple Additive Weighting (SAW) - V.H. Valentino; Adelberta Sarinati; Rudi Prasetya (Institut Bisnis Nusantara, 2026)
Selecting a boarding house that meets the preferences and needs of the occupants can be a challenging task due to the many factors that need to be considered, such as location, facilities, price, and so on. This research was conducted to design a decision support system for selecting a boarding house room for Mulyadi in the hope of solving the problems experienced by prospective boarding house tenants by applying the Simple Additive Weighting method to the decision support system to assist prospective tenants in the boarding house room selection process. A Decision Support System (DSS) is one approach that can assist in the boarding house room selection process. The Simple Additive Weighting (SAW) method is a fairly simple and effective method for addressing this selection problem. The data used includes criteria frequently considered by prospective boarding house tenants, such as rental price, availability of facilities, security, room location, and other criteria considered important. The final research steps carried out by the author were to enter the weight values ​​of the criteria and alternatives, perform calculations, and rank the alternatives. The calculation results showed that Room 03 was the best alternative with the highest preference value of 96.